School Literacy Movement Management to Improve Indonesian Language Learning Achievement in Elementary Schools - Sri Wahyani; Wiwik Dyah Aryani (ITScience (Information Technology and Science), 2026)
This study aims to analyze the management of the School Literacy Movement (Gerakan Literasi Sekolah/GLS) in improving Indonesian language learning achievement in elementary schools. The research employed a qualitative approach with a multisite case study design conducted at SDN Semanan 15 and SDN Pegadungan 11 Jakarta. Data were collected through in-depth interviews and document analysis involving school principals, teachers, and library staff. Data analysis was carried out using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that literacy movement management is implemented through four main stages: planning, organizing, actuating, and controlling. In the planning stage, literacy programs are designed either in a structured, routine manner or through creative, integrative approaches. In the organizing stage, collaboration among teachers, students, and parents supports the implementation of literacy activities. In the implementation stage, literacy programs are carried out through routine reading habits and creative activities such as storytelling, drama, and performance-based literacy. In the controlling stage, evaluation and follow-up actions are conducted through structured and performance-based assessments to ensure program effectiveness. The study concludes that literacy movement management contributes positively to improving students’ Indonesian language learning achievement, particularly in reading comprehension, writing skills, communication ability, and self-confidence. However, its effectiveness is influenced by factors such as teacher competence, stakeholder collaboration, and resource availability. Therefore, strengthening management practices and integrating structured and creative literacy activities are essential to optimizing literacy development in elementary education.